Designing of lampshade with 3D CG application and manufacturing of designed shape in graphic science education. (10th April 2015) - Suzuki, Hirotaka; Sakaki, Ai; Yasufuku, Kensuke; Matsumoto, Takashi
In graphic science education, understanding of knowledge about shape and light is quite significant. However, students find it difficult to learn the function of the shapes and actual brightness distribution in graphic science education with computer aided design (CAD) and three–dimensional computer graphics (3DCG) education. To improve this situation, we introduced model manufacturing of lampshade into graphic science education. First, students should decide curved line on graph paper by hand and decide coordination of control points of the curved line. Secondly, students input both the coordination data of the points and number of frames. Then, 3DCG application generated CG perspective view of the lampshade, drawing of lampshade frame and drawing of development of curved lampshade surface from these data. Finally, students should manufacture paper model of the lampshade with printed drawings. In this paper, we explain the objective of the class, schedule of the class, detailed content of the lampshade designing exercise, submitted CG drawings and paper models and result of class evaluation by students.